Proceedings of the ACM SIGMETRICS/international Conference on Measurement and Modeling of Computer Systems 2013
DOI: 10.1145/2465529.2479781
|View full text |Cite
|
Sign up to set email alerts
|

Elastic paging

Abstract: We study a generalization of the classic paging problem where memory capacity can vary over time -a property of many modern computing realities, from cloud computing to multi-core and energy-optimized processors. We show that good performance in the "classic" case provides no performance guarantees when memory capacity fluctuates: roughly speaking, moving from static to dynamic capacity can mean the difference between optimality within a factor 2 in space, time and energy, and suboptimality by an arbitrarily l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Accordingly, much research has been devoted to understand and analyze caching algorithms that work well in practice [4,1,17]. Recently, there has been some interest in developing caching algorithms for cloud computing scenarios [18,5]. The latter references consider scenarios where the memory available to an algorithm can vary over time.…”
Section: Related Workmentioning
confidence: 99%
“…Accordingly, much research has been devoted to understand and analyze caching algorithms that work well in practice [4,1,17]. Recently, there has been some interest in developing caching algorithms for cloud computing scenarios [18,5]. The latter references consider scenarios where the memory available to an algorithm can vary over time.…”
Section: Related Workmentioning
confidence: 99%
“…Related Work on Green Paging. The last decade has seen a surge in interest for paging models where memory capacity is not static, but can instead change over time [2,4,5,9,14,21,25,26]. One justification for such models is the increased popularity of virtualization/cloud services: the amount of physical memory allotted to a specific virtual machine often varies considerably over time based on the number and priority of other virtual machines supported by the same hardware.…”
Section: Introductionmentioning
confidence: 99%
“…This problem has been investigated by López-Ortiz and Salinger [21] and later, in the more general version where pages have sizes and weights, by Gupta et al [14]. Subsequent work, and in particular the elastic paging of [25,26], showed that one can effectively decouple page replacement from memory allocation: even if the latter is chosen adversarially, LFD is still optimal, and a number of well-known paging algorithms like LRU or FIFO are optimally competitive, with a competitive ratio that is extremely close albeit not quite equal to the classic k/(k − h + 1). A similar line was taken by adaptive caching [5] with a slightly different cost model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation